Body Fatness Influences Associations of Body Composition and Energy Expenditure with Energy Intake in Healthy Women. Issue 1 (16th November 2020) - Casanova, Nuno; Beaulieu, Kristine; Oustric, Pauline; O'Connor, Dominic; Gibbons, Catherine; Duarte, Cristiana; Blundell, John; Stubbs, R. James; Finlayson, Graham; Hopkins, Mark
Abstract : Objective: This study aimed to investigate the influence of body fatness on the associations of body composition and energy expenditure (EE) with energy intake (EI). Methods: Data from 93 women (BMI = 25.5 [SD 4.2] kg/m 2 ) recruited for two studies (Study 1, n = 48, BMI = 25.0‐34.9 kg/m 2 ; Study 2, n = 45, BMI = 18.5‐24.9 kg/m 2 ) were examined. Body composition, resting metabolic rate (RMR), and test meal EI were assessed during a laboratory probe day. Physical activity, total daily EE (TDEE), and self‐reported free‐living 24‐hour EI were collected during 7 days. Results: In the whole sample, fat‐free mass ( r = 0.45; P < 0.001), RMR ( r = 0.41; P < 0.001), and TDEE ( r = 0.39; P < 0.001), but not fat mass ( r = 0.17; P = 0.11), were positively associated with free‐living 24‐hour EI. Body fat percentage moderated the associations of RMR (β = −1.88; P = 0.02) and TDEE (β = −1.91; P = 0.03) with mean free‐living 24‐hour EI. Fat mass was negatively associated with test meal EI only in the leaner group ( r = −0.43; P = 0.004), and a weak nonlinear association was observed in the whole sample ( r 2 = 0.092; P = 0.04). Conclusions: Body fat percentage appears to moderate the associations between EE and daily EI. Furthermore, the negative association between fat mass and test meal EI observed in leaner individuals was absent in those with higher body fatness. Therefore, higher levels of body fatness may weaken the coupling between EE and EI.